Estudo comparativo das diferentes classificações histológicas do grau de diferenciação no adenocarcinoma de endométrio - Erica Becker de Sousa Xavier (2010)
Introduction: The histological grade is one of the main prognostic factors in the endometrial adenocarcinoma and it is also important to the surgical planning and to the recommendation of complementary therapy. Even though there are well established criteria for the determination of this histopathologic finding, the interpretation can present some subjectivity. The objective of this study is to assess the different histologic classifications of the tumoral grade in women suffering from endometrial adenocarcinoma. Methods: 70 patients who were suffering from endometrial adenocarcinoma and who had had surgical treatment were studied. The slides of the tumor were classified according to the tumoral grade based on the criteria of FIGO, modified FIGO (binary system), Lax and ALKUSHI. The slides were assessed by two pathologists and by the same pathologist in two separate occasions. The tissue was processed for immunohistochemical evaluation of Ki-67.Inter- and intraobserver agreement was assessed by kappa statistics. X2 tests were used to analyze 2 x 2 or 2 x 3 tables considering p < 0,05 significant. Results: The tumoral grading (FIGO) was foi IA in 42 (60%) patients, IB in 19 (27,1%), IIA in 3 (4,3%), IIB in 1(1,4%), IIIA in 4 (5,7%) e IIIC in 1 (1,4%). Theintraobserver agreement was moderate according to the FIGO grading system (k: 0,469 e 0,538); substantial according to the modified FIGO grading system (k: 0,661 e 0,768), moderate according to the binary grading of LAX (k: 0,496 e 0,466) and moderate/substantial according to the grading system of ALKUSHI (k: 0,528 e 0,736). In the interobserver assessment, the agreement was fair according to the FIGO grading system (k= 0,271 e 0,343); substantial/moderate to the modified FIGOgrading system (k = 0,661 e 0,522); fair/moderate according to the binary grading of Lax (k = 0,258 e 0,465); fair according to the grading system of Alkushi (k = 0,283 e 0,402). There was no association of the histologic FIGO grading system (p =0,663), modified FIGO grading system (p = 0,370);binary grading of Lax ( p = 0,402) and the grading system of Alkushi (p = 0,101) with the tumoral stage (FIGO). There was association of the histologic FIGO grading system (p =0,039), modified FIGO (p=0,017) and ALKUSHI (p =0,039) with Ki-67 expression. Conclusion: The histologic grading systems in the endometrial adenocarcinoma presented high subjectivity. The modified FIGO grading system presented a better intra- and interobserver agreement